Do tripé macroeconômico à nova matriz econômica: uma análise da taxa de juros natural do Brasil - Silva, Matheus Teodoro Gaglianone da (2019)
This study has the aim to analyze the trajectory of natural rates of Brazilian from a Taylor's dynamic rule. In order to reach the proposed objective, filtering instruments were used to extract the natural rate in five different ways, especially through the Kalman Filter technique. This study also evaluates the periods of the Macroeconomic Tripod and the New Macroeconomic Matrix, as well as their differences in terms of economic policy and macroeconomic variables. The period under review is comprehended between the third quarter of 2001 and the first quarter of 2018. The main conclusions are: i) the real interest rate was kept below its natural rate between early 2011 and mid-2013 which caused inflationary pressure in the following years. After the collapse of the New Economic Matrix in 2014 these rates have again approached.; ii) the natural interest rate was 2.82% for the first quarter of 2018.